2011
DOI: 10.1016/j.febslet.2011.10.001
|View full text |Cite
|
Sign up to set email alerts
|

MosquitoAedes aegypti(L.) leucokinin receptor is critical forin vivofluid excretion post blood feeding

Abstract: a b s t r a c tThe evolution of the blood feeding adaptation in mosquitoes required hormonal coordination of multiple physiological processes (behavior, digestion, diuresis, oogenesis). The Aedes kinins (leucokinin-like neuropeptides) are involved in post blood feeding physiological processes, having diuretic and myotropic functions. To understand the in vivo contribution of the kinin receptor to overall female post-prandial fluid excretion, RNAi knockdown was followed by fluid secretion assays which proved it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…We found that AKIII did not detectably modulate contractions of the crop. Consistent with this negative data, mRNAs encoding the kinin receptor are weakly expressed in the crop of D. melanogaster , and kinin or kinin-receptor immunoreactivities have not been reported in the crop of D. melanogaster or A. aegypti (Al-Anzi et al 2010; Chintapalli et al 2007; Kersch and Pietrantonio, 2011). …”
Section: Discussionsupporting
confidence: 76%
“…We found that AKIII did not detectably modulate contractions of the crop. Consistent with this negative data, mRNAs encoding the kinin receptor are weakly expressed in the crop of D. melanogaster , and kinin or kinin-receptor immunoreactivities have not been reported in the crop of D. melanogaster or A. aegypti (Al-Anzi et al 2010; Chintapalli et al 2007; Kersch and Pietrantonio, 2011). …”
Section: Discussionsupporting
confidence: 76%
“…These tissues also displayed elevated Ca 2+ in response to myokinin, demonstrating novel roles for these neuropeptides (Radford et al, 2002). In A. aegypti the myokinin receptor was shown to be critical for in vivo fluid excretion post blood feeding (Kersch and Pietrantonio, 2011). In Drosophila the receptor was shown to be involved in appetite, chemosensory responses, and metabolism (Al-Anzi et al, 2010; de Haro et al, 2010; Cognigni et al, 2011; LĂłpez-Arias et al, 2011).…”
Section: Deorphanized Neuropeptide Receptorsmentioning
confidence: 99%
“…1), especially in relation to signalling cascades initiated by neuropeptides . Mosquito tubules also contain principal and stellate cells, and research into cell signalling mechanisms in mosquito tubules has revealed important insights into control of epithelial function in blood-feeding insects via both cell types (Coast et al, 2005;Kersch and Pietrantonio, 2011;Pollock et al, 2004;Radford et al, 2004;Schepel et al, 2010).…”
Section: The Malpighian Tubules As Stress Sensorsmentioning
confidence: 99%